Justice and algorithms: An ethical and legal analysis of Law 31814 on artificial intelligence in Peru (Forseti. Law Review, 2025)
The incorporation of artificial intelligence into the judicial system raises tensions with constitutional principles such as due process, the reasoning of decisions, and the guarantee of a natural judge. From an ethical-legal perspective, this article examines Law No. 31814, highlighting its normative insufficiencies in addressing algorithmic risks, and proposes criteria for a substantively just regulation.
Keywords: Artificial intelligence; Algorithmic justice; Biases; Legal regulation; Judicial ethics